Plasticity of intrinsic excitability in mature granule cells of the dentate gyrus - Lopez-Rojas, Jeffrey (Sci Rep, 2016)
The dentate gyrus is the main entry gate for cortical input to the hippocampus and one of the few brain areas where adult neurogenesis occurs. Several studies have shown that it is relatively difficult to induce synaptic plasticity in mature but not in newborn dentate granule cells. In the present work we have systematically addressed how classical protocols to induce synaptic plasticity affect action potential firing and intrinsic excitability in mature granule cells. We found that stimulation paradigms considered to be relevant for learning processes consistently modified the probability to generate action potentials in response to a given synaptic input in mature cells, in some paradigms even without any modification of synaptic strength. Collectively the results suggest that plasticity of intrinsic dendritic excitability has a lower induction-threshold than synaptic plasticity in mature granule cells and that this form of plasticity might be an important mechanism by which mature granule cells contribute to hippocampal function.